On-line measurement method of transmission backlash based on angular velocity and double-end angular position information. (January 2021) - Li, Ming; Liang, Ruirui; Zhang, Yanshun; Peng, Chuang; Mu, Dong; Wan, Zhen
Backlash is the inherent characteristic of gear transmission system. It is an important mean to measure and compensate backlash to improve transmission performance. When the driving gear reverses, due to the existence of backlash, the driven gear will still keep its original steering due to inertial motion until the driven gear collision with the driving gear. In this paper, based on the analysis of the tooth gap of the driving gear and the driven gear, an on-line measurement method of the meshing tooth gap combining the angular velocity of the load end with the information of the Angle position of the two axes of the master-slave gear is presented. This method uses the gyroscope at the load end (driven wheel) to monitor the sudden change of angular velocity at the moment of gear reverse impact and re contact, and the signal is used as the judgment basis for the reverse contact moment of the driving gear and driven gear. Then, the angular position data of driving gear and driven gear are fused at the time of reverse rotation and contact impact, and the backlash of the gear is calculated online. Finally, setting up an experimental platform for measuring backlash, and the proposed method is verified. The experimental results show that the proposed method can achieve accurate backlash measurement.